Effect of freeze-dried and encapsulated caigua (Cyclantera pedata) on cholesterol levels in male subjects between 40 and 65 years old - Lizaraso Soto, María del Rosario (2022)
To determine the effect of caigua (Cyclantera pedata) , in serum cholesterol and lipid profile under an ad libitum diet, a simple blind trial was designed, administering liophilized caigua capsules (400 mg of concentrated extract ofl OOg of natural caigua) for 45 days, to 25 hypercholesterolemic men aged 40 to 65 years old. Subjects were divided into five groups who received different dose of caigua. Serum total cholesterol, low density lipoprotein cholesterol, high density lipoprotein cholesterol and triglyceride were measured.The treatment with four capsules, reduced significantly the total cholesterol, in a mean of 93 mg/dL or 33,8% of initial value. Reduction of LDL cholesterol was 88 mg/dL or 44,5% of initial value. Variations of HDL cholesterol and triglycerides were not significant.